Examen especial a la cuenta inventario de mercaderías de la empresa Celcos comercial de la ciudad de Loja periodo 01 enero al 31de diciembre del 2012 - Campoverde Sanmartín, Alcides Adalberto (2014)
This research is entitled "Special Consideration to the inventory account of goods Business Celcos Commercial of Loja city period January 1st to December 31th, 2012" is based on an objective examination of the operations performed by company which will serve as a significant contribution to the improvement and control of inventories account. Likewise accomplish with the proposed objectives, the three phases of audit was conducted to verify compliance with applicable laws in the execution of the activities developed by obtaining the evidence to support my opinion in the formulation of the final report with comments, conclusions and recommendations. Similarly it was shown that the level of risk in Celcos Company Commercial regarding the inventory account is high and a low level of confidence for this reason it is recommended that continuous monitoring of returns to suppliers and entry of merchandise in order to have better control of existing inventories.